2017
DOI: 10.3892/or.2017.6059
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of the combination of 5-Aza‑CdR and suberoylanilide hydroxamic acid on the anticancer property of pancreatic cancer

Abstract: Despite increasing advances in the diagnosis and treatment for pancreatic cancer, the mortality rate remains high world-wide. There is an urgent need for new therapies to improve survival and quality of life for pancreatic cancer patient. Epigenetic therapeutic agents such as 5-Aza‑CdR and suberoylanilide hydroxamic acid (SAHA) have shown therapeutic effects for human cancers. We evaluated the efficacy of 5-Aza‑CdR or SAHA and their combination as potential therapies for pancreatic cancer in vitro. Treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Western blot analysis was conducted as previously described [ 11 ]. The primary antibodies were as follows: anti-AGO2 (1:1000), anti-ZEB1 (1:1000, Cell Signaling Technology, Beverly, MA, USA), and anti-β-Actin (1:2500, Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was conducted as previously described [ 11 ]. The primary antibodies were as follows: anti-AGO2 (1:1000), anti-ZEB1 (1:1000, Cell Signaling Technology, Beverly, MA, USA), and anti-β-Actin (1:2500, Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…1113 In this context, DNA hypomethylating agents, such as azacitidine and decitabine, have been used in the clinic setting for decades as anticancer therapy for several tumors. 1416 Histone deacetylase inhibitors (HDACi) are also an emerging class of cancer therapies. 1720 Moreover, several lysine methyltransferases and demethylases have been identified as promising targets for pharmacological intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In-vitro studies have shown that 5-Aza-CdR, a DNA methyltransferase 1 (DNMT1) inhibitor, could induce cell death and apoptosis of pancreatic cancer cells by reactivation of RASSF1A and up-regulation of Bax genes (36). Han et al also observed the synergistic effects of the combination of 5-Aza-CdR and suberoylanilide hydroxamic acid on the anticancer property of PC (37). More inspiring, phase I/II clinical trials of DNMT1 inhibitors (azacitidine, decitabine and guadecitabine) in PC patients were currently underway, the inhibitors of which exhibited potential treatment outcomes (38).…”
Section: Discussionmentioning
confidence: 99%